Anesthetic block for cataract surgery (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Worldwide, cataracts are one of the leading causes of blindness. Local anesthesia is often used during cataract surgery unless there are medical reasons not to. To achieve local anesthesia, a specific area of the body's nerves are occluded. The procedure entails injecting a local anesthetic into the tissue around the nerve. In the eye, the retrobulbar and peribulbar approaches are the two most common. The effectiveness and safety of the peribulbar method compared to the retrobulbar block in administering anesthesia for cataract surgery is a matter of some contention. Examining the differences between peribulbar (PB) and retrobulbar (RB) anaesthesia in terms of pain levels, patient acceptance, and ocular and systemic consequences was the goal of this study. Clinical studies that compared peribulbar and retrobulbar anesthesia for cataract surgery were included in our meta-analysis. Neither retrobulbar nor peribulbar anesthesia was associated with a different level of perceived pain during surgery. Both had a significant impact. Concerning total akinesia and the need of further injections of local anaesthetic, there was no indication of any change. Relative risk (RR) 2.11, 95% CI 1.46 to 3.05 for conjunctival chemosis and RR 0.36, 95% CI 0.15 to 0.88 for lid haematoma after peribulbar block and retrobulbar block, respectively. Only one patient, who had a retrobulbar block, had the rare occurrence of retrobulbar hemorrhage. Anaesthesia, akinesia, patient acceptance, injection requirements, and the risk of serious complications are all closely related to whether a peribulbar or retrobulbar block is used during surgery. Both varieties of blocks were associated with a low incidence of serious local or systemic problems.